The enhanced performance of capacitive-type humidity sensors based on ZnO nanorods/WS2 nanosheets heterostructure - Dwiputra, Muhammad Adam; Fadhila, Farah; Imawan, Cuk; Fauzia, Vivi (Sensors and actuators. B, Chemical, 2020)
•The novel capacitive-type humidity sensor based on ZnO nanorods/WS2 nanosheets heterostructure was proposed.•The presence of WS2 increased the response and sensitivity and lowered the hysteresis without impacting response and recovery times.•The improved sensor performance might be due to the ability of WS2 to provide more water molecule adsorption sites.•The interface of ZnO/WS2 contains high local charge density and an internal electric field that increase the water dissociation rate. Zinc oxide (ZnO) is a promising candidate for humidity-sensing materials due to its low-cost preparation, superior chemical and thermal stability, controllable surface morphology, and low water solubility. However, pristine ZnO-based humidity sensors suffer from poor response and large hysteresis that limit their application. In this study, n-type semiconducting tungsten disulfide (WS2) was utilized to form ZnO nanorods/WS2 nanosheets heterostructure grown on indium tin oxide coplanar electrode-coated glass substrate. The capacitive-type humidity sensing characteristics were investigated at room temperature. The results show that for humidity ranges of 18–85 % RH, three deposition cycles of WS2 nanosheets onto ZnO nanorods produced significant improvements in the response, sensitivity, and hysteresis with an unchanged response and recovery times compared to pristine ZnO sensors. This improved sensor performance might be due to the ability of WS2 to provide more water molecule adsorption sites. The formation of an n-n junction between ZnO and WS2 created interfaces with high local charge density and built an internal electric field that increase the water dissociation rate. The improved hysteresis might be due to water molecule adsorption on WS2 nanosheets is physical adsorption that facilitates the desorption process.